THE INFLUENCE OF SPINNING WHEEL LEARNING MEDIA ON STUDENT LEARNING OUTCOMES IN SOCIAL SCIENCES (IPS) FOR CLASS VII AT SMP PRIVATE TELADAN PEMATANGSIANTAR IN THE 2024/2025 ACADEMIC YEAR - Dion Rivaldo Sihotang; Herlina Hotmadinar Sianipar; Benjamin Albert Simamora (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the influence of Spinning Wheel learning media on learning outcomes in Social Sciences (IPS) for Class VII students at SMP Swasta Teladan Pematangsiantar. Spinning Wheel learning media is a type of learning media that can create a more enjoyable and engaging learning atmosphere. This research uses a quantitative approach with an experimental method (quasi-experimental) of the Nonequivalent control group design type. The population of this study was all Class VII students at SMP Swasta Teladan Pematangsiantar. The research sample was selected using a purposive sampling technique, which involves selecting samples based on specific considerations that align with the desired criteria to determine the number of samples to be studied. Two classes were involved: an experimental class that used Spinning Wheel learning media and a control class that used a conventional learning model without the aid of media. Student learning outcome data was collected through learning outcome tests (pretest and posttest). The results showed a significant difference between the learning outcomes of students taught using Spinning Wheel learning media and those taught using a conventional learning model without the aid of learning media. The significance values for the pretest of the experimental class were 0.108 and for the posttest of the experimental class were 0.110, while for the pretest of the control class they were 0.104 and for the posttest of the control class they were 0.172. In the Kolmogorov Smirnov column, values > 0.05 indicate that the data is normally distributed. In the homogeneity test, the pretest results for the control and experimental classes were 1.563, and the posttest results for the control and experimental classes were 0.053, meaning the data is homogeneous because it is < 1.882 (F-table) at a significance level of 0.05. In the hypothesis test, the calculated t-value for the pretest of the experimental and control classes was 2.555, and for the posttest of the experimental and control classes, the calculated t-value was 1.712. Comparing these to the t-table value of 1.672, where t-calculated > t-table, it can be concluded that Ha is accepted and Ho is rejected, meaning there is an influence of Spinning Wheel learning media on student learning outcomes. The N-gain test results were 0.553 for the control class with the conventional model, which falls into the medium category, and 0.556 for the experimental class with Spinning Wheel media, also falling into the medium category. The Coefficient of Determination test showed an R-squared value of 0.611, which is close to 1, indicating that Spinning Wheel learning media significantly influences learning outcomes. Thus, Spinning Wheel learning media is effective in improving student learning outcomes in Social Sciences.